A Study on The Ability of The Third Year Students of SMA Negeri 5 Pekanbaru in Writing Analytical Expository Texts - Fadilla Sara Sara; Effendy Gultom Gultom; Maisrul ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:Writing is an important language skill that students should learn in school. Commonly, writing among students takes less attention in the process of its activities. They tend to take a long process and unorganized result. The aim of this descriptive research is to find out the ability of the third year students of SMA Negeri 5 Pekanbaru in writing analytical expository texts. Beside that, this research also aimed to identify the most difficult and the easiest aspects of analitycal expository texts for the students. The participants of this research are 35 third year students of SMA Negeri 5 Pekanbaru. The data was collected by giving a written test to the students individually. The students were asked to write a good paragraph in term of analitycal expository text. Before doing the test, the students were given a model of analitycal expository texts to remember them about a good form of analytical expository texts. There were five aspects that being assessed in this test, they are grammar, vocabulary, mechanics, organization and fluency. The data were scored by three raters. In analyzing the data, the rater used analytical scoring system that assesses five aspects of writing. The research finding shows that the students have good ability in writing analitycal expository texts with the mean score of 69.5. The easiest aspect for the students in writing analytical expository text is mechanism, while the most difficult aspect is fluency. Keywords :Analytical Expository Texts, Writing Ability